Analysis of User Satisfaction Level of BRI Mobile Application Using Mobile Service Quality with Customer Satisfaction Index (CSI) Method (Case study on Gen Z 1997-2012 in Makassar City) - Roreng, Petrus Peleng; Gala, Geraldo Tandi (Master of Management Study Program, Universitas Kristen Indonesia Paulus, 2025)
BRImo currently presents a variety of services that will facilitate its users in conducting banking transactions. The problem in this study is that the system often experiences errors and based on reviews on Google Playstore there are many responses from users to the application. Because there are still some complaints and unsatisfactory assessments, it is necessary to conduct research on user satisfaction to find out how high user satisfaction with the BRImo application is. The method used in this study uses the Customer Satisfaction Index (CSI) method to measure the percentage of satisfaction of BRImo application users. This study will use the dimensions contained in the quality of cellular services that have been modified to suit the object under study in this study. The data used to be processed in this study were obtained from the results of a questionnaire totaling 15 questions. The number of respondents in this study were 96 respondents. After the data is collected from the respondents, the data will be tested for validity and reliability to find out how valid and reliable the data will be processed by the CSI method. The results of this study can be seen in the calculation of the CSI method obtained a percentage of user satisfaction of 83.59% and it can be stated that customers feel “Very Satisfied” with the quality of service of the BRImo application.